Identificaç\~ao de mercados geográficos e construç\~ao de indicadores de concorrência no setor portuário Brasileiro - Alexandre Ywata de Carvalho; Paulo C. Coutinho; André L. Oliveira; Paulo Augusto P. de Britto; Paulo Roberto Barbosa Lustosa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– In this paper, we analyze the structure of geographic markets for the port sector in Brazil, identifying influence areas for its main ports. We employed spatial clustering algorithms, based on foreign trade data. We observed that the geographic factor seems to be extremely important in determining which port to use to export Brazilian products or to import foreign cargo. In general, port competition seems to be more pronounced in federation states away from the coast. For states on the coast, exporting and importing companies seem to choose ports within their own states or in neighboring federation units. The great importance of the geographic proximity may be directly related to the high surface transportation costs observed in Brazil. Based on the identified geographic markets for the ports sector, we can then proceed with calculating competitiveness indicators between ports and within ports (between port terminals). Therefore, we were able to analyze the competition between terminals for ports serving each geographic market. We believe this approach to be more realistic than to analyze only inter port competition. For Port of Santos, which happens to be the biggest port in the country, it has a very high share of imports and exports for cargo consumed or produced in the state of S\~ao Paulo. However, for containers, for example, there are several terminals within Santos, sharing the total amount of operated cargo. This process employed in this paper show the advantage of combining more aggregated import and export information with disaggregated terminal operation data.
Keywords: L11; L13; L52; L91; R42; R12; C02; 330; port sector; geographic markets; hinterlands; competitiveness indicators; spatial clustering algorithms; port terminals; intra and inter port competition